Optimizing Multi-Purpose Vehicle Efficiency for Competitive Advantage in Indonesia’s Automotive Industry - Heri Kusnanto; Jonathan N. Marpaung (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The Indonesian automotive industry, a key economic driver, faces intense competition, with Multi-Purpose Vehicle models dominating due to their suitability for large families and challenging road conditions. This study aims to evaluate the operational and marketing efficiency of seven Multi-Purpose Vehicle models from Brand T, marketed from January 2023 to June 2024, to strengthen market strategy. Using the Data Envelopment Analysis method with an input-oriented Charnes, Cooper, and Rhodes model, the analysis incorporated inputs like marketing, sales, trial unit, and training costs, and outputs including sales volume, market share, and gross profit. Findings reveal that five models achieved maximum efficiency (1.00), with the Multi-Purpose Vehicle segment averaging 0.90, outperforming sport utility vehicles, hatchbacks, and sedans. This efficiency stems from alignment with Indonesia’s socio-economic needs, including price sensitivity and demand for durable, high-capacity vehicles. The study concludes that Brand T should prioritize resource allocation and innovation in Multi-Purpose Vehicles, repositioning less efficient models and using them as branding substitutes for halo cars. These strategies enhance profitability and competitiveness in Indonesia’s price-sensitive market, reinforcing Multi-Purpose Vehicles as a strategic cornerstone.